The Too-Big-To-Fail Problem: The Case of the Post-Crisis Banking System in Iceland - Snorri Páll Gunnarsson 1995- (2016)
This thesis aims to assess the issue of too-big-to-fail (TBTF) banks in the Icelandic banking system from 2008 and to the present. It attempts to gauge the extent to which the issue is relevant to the current banking system. TBTF has become a shorthand for, among other things, banks that uninsured creditors expect the government to protect in the case of failure in light of their systemic importance and interconnectedness, as well as the high cost associated with their exit from the market. Such expectations, as well as alternatively the invalidation or vindication of those expectations, have far-reaching implications for financial stability, the broader economy and societal welfare. The implications constitute the TBTF problem. Following an overview of the theoretical framework surrounding the essential features of the TBTF issue, the TBTF problem in the post-crisis banking system in Iceland is assessed both quantitatively and qualitatively. Several sources of moral hazard are identified, including an unbinding blanket guarantee of domestic deposits still outstanding, the existence of an explicit lender of last resort within capital controls, and pre-crisis plans to nationalize and support a significant part of the banking system. An analysis of the banks’ financial statements between 2008 and 2015 reveals several trends that support and contradict the TBTF problem, suggesting that the largest banks are not maximizing the value of their implicit safety net. Trends and approximations consistent with the TBTF hypothesis include increased systemic importance of the three largest banks operating in the banking sector, deposit-funding advantages for the largest banks and greater risk-taking in non-core activities. Contradictory trends include less risk-taking in the banks’ loan portfolios as well as less interconnectedness in the interbank market. An attempt will also be made to harmonize the contradictory quantitative trends with exogenous factors that constrain the banks form maximizing the value of their implicit ...